Research Trends On High Order Thinking Skills (HOTS) In Arabic Language Education Journals In Indonesia/ Tren Penelitian High Order Thinking Skills (HOTS) Pada Jurnal Pendidikan Bahasa Arab Di Indonesia - Wahyudi, Hakmi; Agustiar, Agustiar; Azhar, Muhammad; Yusriyah, Yusriyah; Yusra, Nelly (Ijaz Arabi Journal of Arabic Learning, 2024)
Higher Order Thinking Skills (HOTS) are considered essential skills in the modern era, encompassing the abilities to think critically, analytically, and creatively and to solve problems. HOTS is crucial to understanding cultural heritage, literature, and Islamic thought in Arabic language learning. This study aims to gather and review information from various research studies that discuss HOTS in Indonesia using content analysis methods on articles published in Science and Technology Index (SINTA) accredited Arabic language education journals from 2019 to 2023. This research addresses questions about HOTS research trends in terms of the number of studies per year, the accreditation of journals publishing HOTS articles, types of research, research subjects, data collection instruments, and data analysis techniques used by researchers. The results of this study show an increasing trend in HOTS research. Researchers tend to prefer publishing their findings in accredited journals to enhance the credibility and exposure of their research. Qualitative research designs dominate, with documentation as the primary data collection instrument. Practice questions in textbooks and exam questions containing HOTS dominate the research objects. This impacts the data analysis techniques, with content analysis methods providing a clear framework for exploring meanings and deeply explaining the data context. Based on the research findings, future studies are expected to consider students as research subjects, explore strategies, models, and teaching methods to enhance students' HOTS, increase the variety of research types, and select data analysis techniques.